EFFICACY AND SAFETY OF ACETYLSALICYLIC ACID IN PRIMARY AND SECONDARY PREVENTION OF CARDIOVASCULAR DISEASES - S. N. Tolpygina; S. Yu. Martsevich; E. N. Khoseva; N. V. Kiseleva (Рациональная фармакотерапия в кардиологии, 2015)
Acetylsalicylic acid (ASA) use in the primary and secondary prevention of cardiovascular diseases is focused. Mode of ASA disaggregation action is discussed. Data of randomized controlled trials on ASA efficacy and safety in primary and secondary prevention are presented. The main groups of patients who are required the ASA prevention according to current clinical guidelines are indicated. ASA benefit-risk ratio, as well as ways to improve the safety of antiplatelet therapy are presented, including use of enteric-soluble ASA forms.